2005
DOI: 10.5551/jat.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Cocoa Powder on Atherosclerosis in Kurosawa and Kusanagi-hypercholesterolemic Rabbits

Abstract: We investigated the suppressive effect of cocoa powder (cacao polyphenol content: 7.8%) on atherosclerosis in a spontaneous familial hypercholesterolemic model, Kurosawa and Kusanagi-hypercholesterolemic (KHC) rabbits. Six-month dietary administration of cocoa powder had no effects on body weight, hematology or blood chemistry parameters or a lipid profile in KHC rabbits. Antioxidative activity of lowdensity lipoprotein (LDL) was observed in the 2nd month and 3rd month of administration. Thiobarbituric acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 43 publications
0
34
2
Order By: Relevance
“…The effect of PMS on serum triglyceride level was most significant, which might be applicable for the treatment of hyperlipidemic desease in the future. In cholesterol-fed rabbits, increased serum total cholesterol level has been reported to be due, in most part, to increased chylomicron remnant and / or ÎČ-VLDL cholesterol, which might be involved in the promotion of atherosclerosis (13). However in this study, the hyperlipidemic pattern induced by high fat diet showed both increased cholesterol and triglyceride levels.…”
Section: Discussioncontrasting
confidence: 49%
“…The effect of PMS on serum triglyceride level was most significant, which might be applicable for the treatment of hyperlipidemic desease in the future. In cholesterol-fed rabbits, increased serum total cholesterol level has been reported to be due, in most part, to increased chylomicron remnant and / or ÎČ-VLDL cholesterol, which might be involved in the promotion of atherosclerosis (13). However in this study, the hyperlipidemic pattern induced by high fat diet showed both increased cholesterol and triglyceride levels.…”
Section: Discussioncontrasting
confidence: 49%
“…According to Hu, [155] dietary polyphenolic supplementation exert desirable outcome in complementary therapy when ingested in large quantity. From the reports of Ranneh et al [156], experimental models confirmed that phenolics from T. cacao exhibited beneficial effects against platelet aggregation [157], high blood pressure [158], atherosclerosis [159], hyperglycemia and hypercholesterolemia [160,161], inflammation [162], hepatocarcinogenesis [160], DNA damage and clastogenic effect [163]. Furthermore, flavonoids and polyphenol from T. cacao such as flavan-3-ols, epicatechin, and catechin are potential inhibitors of pro-inflammatory mediators in tumor necrosis factor-α (TNF-α)-sensitized Caco-2 cells in vitro and exhibited protective effect in colon cancer in vivo [164].…”
Section: Phenols and Phenolic Acidsmentioning
confidence: 91%
“…Genetically hypercholesterolemic rabbits fed cocoa powder (7.8% polyphenol content) for six months showed less LDL oxidation and decreased TBARS compared to animals consuming a control diet (Kurosawa et al 2005). The area of atherosclerotic lesion was significantly smaller in the supplemented group (31%) compared to the control group (52%).…”
Section: Flavanols As Antioxidantsmentioning
confidence: 98%